The nexus between post conflict societies and their capacity to respond to the ebola epidemic in Mano River Union - Hikimatu Tuntei-ya Mohammed; Benjamin Agordzo (Universitas Aisyiyah Yogyakarta, 2021)
The Ebola crisis in the Mano River States and inadequate state responses to the outbreak heightened the challenges post conflict societies face during emergencies. There have been enough literature discussing the issues of Ebola especially in the Mano River Union; however, there is little discussion on the capacity of the Mano River Union to respond to the Ebola epidemic. Against this background, the study sought to investigate the nexus between post conflict societies and their capacity to respond to the Ebola epidemic in the Mano River Union. A non-empirical qualitative case study approach involving extensive review of secondary data in the form of books, journals, internet sites and conference papers was adopted. The results showed that all the countries in the sub-region were unprepared for the outbreak. Even though some countries had disaster management divisions, none had any disaster management plans in place hence the Ebola Virus Disease and its subsequent crisis could not have been anticipated. Following the findings, a strong case has been made for countries in the sub-region to have disaster management plans and other early warning and resilient systems in place in place to reduce the scale of the outbreak and the high number of deaths.